An Effective Academic Administration Model in the Digital Era for Municipal Schools in Udon Thani Province - Thaniniam, Kiticha; Srimuangbun, Adisorn; Sonjai, Songdej (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This study aims to: 1) examine effective academic administration components in the digital era, 2) investigate current and desired conditions of schools under Udon Thani Municipal Administration, 3) develop an effective digital academic administration model, and 4) evaluate the model. Mixed-methods research was employed using questionnaires, interviews, evaluation forms, and focus group discussions. Quantitative analysis used means and standard deviations, while qualitative analysis employed content analysis. Findings revealed: 1) Eight components: digital technology integration in curriculum and instruction, digital leadership and vision, digital competency development, learner achievement and competency focus, data-driven decision making, change management and digital culture creation, professional digital learning communities, and ethical technology use. 2) Current conditions were moderate while desired conditions were high, with highest need in learner achievement focus. 3) The model comprised eight components with clear implementation guidelines and success mechanisms. 4) Evaluation showed highest levels of appropriateness, feasibility, and benefits.